Unexpected phosphorous removal in a Candidatus_Competibacter and Defluviicoccus dominated reactor. (February 2022) - Song, Xia; Yu, Deshuang; Qiu, Yanling; Qiu, Chenguang; Xu, Lingna; Zhao, Ji; Wang, Xiaoxia
Graphical abstract: Highlights: It should cautiously pursue high PRA when aiming at improving PRE. PRE plateaued at 75.68% with influent C/P ratio of 40 mgCOD/mgP. Ca. Competibacter and Defluviicoccus were unexpectedly highly enriched. Ca. Accumulibacter and Tetrasphaera were found absented from EBPR. Abstract: Competition between polyphosphate- and glycogen-accumulating organisms (PAOs and GAOs) is problematic in the enhanced biological phosphorus removal (EBPR) process. Aiming at a high phosphorus removal efficiency (PRE), the phosphorus release amount (PRA) is considered an essential evaluating indicator. However, the correlations between PRE and PRA and the abundance of PAOs are not clear. In this study, the EBPR was established and optimized via adjusting influent carbon to phosphorus ratio (C/P). After 110-day operation, 17.67 mg/L of PRA and 75.86% of PRE simultaneously achieved with influent C/P of 40 mgCOD/mgP. As for PAOs, Candidatus_Accumulibacter and Tetrasphaera were absent, while Hypomicrobium (3.69%), Pseudofulvimonas (1.02%), and unclassified_f_Rhodobacteraceae (2.41%) were found at a low level. On the contrary, Candidatus_Competibacter and Defluviicoccus were unexpectedly enriched with high abundance (24.94% and 16.04%, respectively). These results also suggested that it was difficult to distinguish whether PAOs were enriched merely based on the variations of PRA and PRE.